Dual Laplace - Stieltjes Transformations of Critical Risks in Case of Negative Insurance Payments - Martirosyan, Artak (Mathematical Problems of Computer Science, 2021)
The present paper is devoted to critical risks of collective insurance models with negative insurance payments (connected with contracts with usual life rent). Limit theorems arisen in critical situations are represented and the dual Laplass-Stiltjes transformations are found for critical risks arisen in collective insurance risks models with negative insurance payments. The specifications of the considered collective risk model and the adaptive control strategy for multiperiodic insurance risk model introduced by Malinovskii is illustrated.